Peculiarities in treatment of patients with false joints of long bones in conditions of hyperhomocysteinaemia and associated states - Korzh, Mykola; Bezsmertniy, Yuriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The purpose of the present work was to improve the treatment of reparative osteogenic disorders on the basis of study of the effect of hyperhomocysteinaemia (HHcy) and associated metabolic and molecular-genetic factors in the formation of false joints of long bones. The efficacy of surgical treatment was assessed in 153 patients with false joints of long bones against a background of HHcy and associated states. HHcy and metabolic disorders were diagnosed in 81, HHcy and molecular-genetic disorders in 72 patients. It was revealed that, against a background of HHcy and associated metabolic and genetic disorders, surgical treatment of false joints was complicated by inflammatory and thrombus obliterating diseases of vessels. The course of reparative osteogenesis was characterized by a sharp inhibition of the osteoinductive potential of the bone tissue with progression of local and systemic osteoporosis, development of an instability in fixing structures, delays in the formation, mineralization and organotypical reconstruction of distraction regenerate, appearance of refractures. A combination of HHcy and polymorphism of 677-TT MTHFR and 786 SS-NOS genes created the most unfavorable conditions for osteoreparation. Treatment of false joints against a background of HHcy depended upon the clinical-radiological type of a false joint, polymorphism of MTHFR C677T and eNOS Ò786Ñ genes, state of trophism of bone fragments and their spatial position, consisting in use of the rational surgical technique, an active management of the pre- and postoperative periods, involvement of metabolic and osteotrophic therapies.